PREVALENCE AND RISK FACTORS OF HPV INFECTION AMONG WOMEN OF REPRODUCTIVE AGE IN SURABAYA: Prevalensi dan Faktor Risiko Infeksi HPV Pada Wanita Usia Reproduksi di Surabaya - Widayati, Umi; Qurniyawati, Eny; ElKhalil, Rouwida (Universitas Airlangga, 2026)
Background: Human Papillomavirus (HPV) is a group of viruses that can infect the genital tract and cause various health conditions, including malignant cervical cancer. According to data from the Global Burden of Cancer (GLOBOCAN) 2022, cervical cancer ranks as the second most common cancer among women in Indonesia after breast cancer, with approximately 36,964 cases. Purpose: This study aimed to determine the prevalence and identify the risk factors of HPV infection among women of reproductive age. Methods: A quantitative, cross-sectional study was conducted, involving 300 vaginal swab samples collected via self-sampling. HPV detection was performed using Polymerase Chain Reaction (PCR) to identify HPV DNA and determine its genotypes. Chi-square tests were applied to analyze the effects of age, age at first sexual intercourse, age at first pregnancy, number of deliveries, and contraceptive use, particularly hormonal contraceptives, on the incidence of HPV infection. Results: A total sampling of 300 women of reproductive age, predominantly other subtypes (8.33%), subtype 16 (1.33%) and subtype 18 (1.00%). Significant associations were found between age at first pregnancy (OR = 0.006, 95% CI = 0.001–0.045, p = 0.000) and hormonal contraceptive use (OR = 0.653, 95% CI = 0.250–1.709, p = 0.030). with HPV infection. Conclusion: These findings indicate that age at first pregnancy and hormonal contraceptive use are significantly associated with HPV infection, highlighting the urgent need for expanded HPV vaccination programs, routine screening, and targeted education on HPV risk, contraceptive choices, and pregnancy planning in Surabaya.